Experimental study of local scour around complex bridge piers - Castiblanco, M. (2011)
This poster shows the partial results of research on local scour around complex piers. Results include the complex pier configuration (geometry and relative location with respect to bed), the methodology used to calculate the contribution of each complex pier component on scour depth, the scour hole evolution and the maximum scour depth evolution.